Assessing Industry Risk by Ratio Analysis: A Comment. - Blocher, Edward; Chen, Kung H. (The Accounting Review, 1978)
Falk and Heintz have proposed a scalogram technique to rank industries according to risk as reflected by financial ratios. The present paper examines some problems which need to be resolved before this technique can be used. First, the F & H selection of ratios is somewhat subjective and is not supported by tests for validity and reliability. And because of the confounding effects of changing economic conditions, the difficulty in obtaining a unique observable concept for industry risk, and because of measurement problems, it may be infeasible to assure an adequate degree of validity and reliability for this ranking technique. Also, some of the ratios selected by F & H may have high inter-correlation with other F ratios, thus implicitly adding greater weights to some of the ratios. Moreover, the F & H technique may be biased because of the selection of a different number of significant digits for two of the ratios. F & H have not offered any supporting reason for either of these sources of bias.